2016
DOI: 10.1108/jcm-09-2015-1546
|View full text |Cite
|
Sign up to set email alerts
|

Guiding when the consumer is in control: the moderating effect of adaptive selling on the purchase intention of the multichannel consumer

Abstract: Purpose The purpose of this paper is to investigate the impact of adaptive selling (AS) when “click and brick” in control multichannel consumers (MCCs) encounter in-store salespeople. Design/methodology/approach An online survey was administered to 387 college students from several southeastern colleges in the USA. The study consisted of a single manipulated factor (AS: high vs low) and a second measured factor (degree of MCC search: high vs low). Covariance-based structural equation modeling was selected an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 56 publications
0
16
0
1
Order By: Relevance
“…PC is presumed to influence one's intention (Lunardo & Mbengue, ). In fact, increases in PC have been empirically linked to PI with conventional consumers (Kokkinaki, ; Lunardo & Mbengue, ) and multi/omni‐channel consumers (Rippé et al., ; Rippé, Weisfeld‐Spolter, Yurova, Hale, & Sussan, ). Also, Dickinger and Kleijnen () found that PC affects Austrian consumers’ intention to redeem mobile coupons.…”
Section: Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…PC is presumed to influence one's intention (Lunardo & Mbengue, ). In fact, increases in PC have been empirically linked to PI with conventional consumers (Kokkinaki, ; Lunardo & Mbengue, ) and multi/omni‐channel consumers (Rippé et al., ; Rippé, Weisfeld‐Spolter, Yurova, Hale, & Sussan, ). Also, Dickinger and Kleijnen () found that PC affects Austrian consumers’ intention to redeem mobile coupons.…”
Section: Hypothesesmentioning
confidence: 99%
“…Rippé et al. () ascertained a full mediation effect between multichannel consumer searching and purchasing behavior. Lala and Chakraborty () aver that when consumers view themselves as in control, they will increase search efforts, and such efforts will oblige consumers to remain in the buying situation as well as augment their spending.…”
Section: Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…For organisations to effectively compete in their markets, both traditionally and electronically, substantial quantities of customer data are required; with the increased accessibility and storage of electronic customer data, consumers express heightened privacy concerns (Groß, 2015;Palmer, 2005). 'Privacy' is the right to prevent disclosure of personal information to others through exerting control over its collection, use, access and release (Bélanger & Crossler, 2011;Bélanger et al, 2002;Peer & Acquisti, 2016;Rippé et al, 2016). Privacy concerns become prominent when information disclosure is requested, primarily due to fears that their information may be intercepted or misused (Aguirre et al, 2016;Roca et al, 2009).…”
Section: Privacy and Security Concernsmentioning
confidence: 99%
“…Rather, security concerns relate to being free from threats of fraud whereas privacy concerns relate controlling situations to reduce risks of being disturbed, observed or intruded by others. For example, security concerns may involve situations whereby consumers fear the safety of their personal information within a company database whereas privacy concerns relate to the fears of their inability to control the exploitation and sharing of their information (Alharbi et al, 2013;Rippé et al, 2016). Table IV draws attention to discrepancies towards differentiations between security and privacy concerns and demonstrates situations where they are considered collaboratively and when then are not.…”
Section: Privacy and Security Concernsmentioning
confidence: 99%